(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate and compare the post-operative functional outcome of patients of intertrochanteric fractures of femur undergoing either dynamic hip screw (DHS)or proximal femoral nail (PFN) fixation presenting under spinal anesthesia in tertiary care hospital. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of orthopedic, Unit I and Department of Anesthesia Mohi-ud-Din Teaching Hospital Mirpur AJK from March 2016 to April 2017. Materials and Methods: One hundred and fifty male and female patients fulfilling inclusion criteria presenting in orthopedic department. Their bio-data was recorded followed by an objective assessment of the intertrochanteric fracture of femur. Seventy-five patients underwent fixation with proximal femoral nail and 75 patients underwent fixation with dynamic hip screw by lottery method. Patients were objectively assessed first at 2 weeks post-operatively and then at 4 weekly intervals for up to 24 weeks for functional outcome in terms of Kyle’s criteria for good to excellent results. Results: Mean age of patients in dynamic hip screw group and proximal femoral nail group was 61.29±11.94 and 59.10±13.61 years respectively. In Group A, 25(33.34%) patients mode of injury was trauma due to road traffic accident and 50(66.64%) patients mode of injury was fall at home whereas in Group B 28(37.34%) patients had trauma due to road traffic accidents and 47(62.66%) were injured due to fall. Functional outcome was assessed by using Kyle’s criteria. At 8th, 12th, 20thand 24th week good to excellent functional outcome was significantly high in Group B as compared to Group A patients. (8th week: 26.67% vs. 44%, 12th Week: 36% vs. 52%, 20th Week: 85.33% vs. 100%, 24th Week: 92% vs. 98.66%) while at 16th week functional outcome was although high in Group-B patients but it was not statistically significant. (16th Week: 81.34% vs. 89.34). Conclusion: Proximal femoral nail is far better implant in terms of post-operative functional outcome as compared to dynamic hip screw for treating intertrochanteric femoral fractures. i.e. (Kyle’s Criteria at 24th Week: DHS: 92% vs. PFN: 98.66%).